Ageism Linked to Culture, Not Demographics: Evidence From an 8-Billion-Word Corpus Across 20 Countries. (25th October 2020) - Ng, Reuben; Lim-Soh, Jeremy W
Abstract: Objectives: Ageism has increased over 200 years and costs the U.S. health care system $63 billion a year. While scholars agree on the consequences of ageism, there are disagreements on whether it is related to the demographics of aging, or society's cultural values. We test both hypotheses across 20 countries. Method: To circumvent the sampling limitations of survey studies, we used an 8-billion-word corpus, identified 3 synonyms with the highest prevalence—aged, elderly, old people—and compiled the top 300 words (collocates) that were used most frequently with these synonyms for each of the 20 countries. The resulting 6, 000 collocates were rated on an ageism scale by 2 raters to create an ageism score per country. Cultural dimension scores—Power Distance, Individualism, Masculinity, Uncertainty Avoidance, and Long-term Orientation—were taken from Hofstede, and demographics—size and speed of population aging—came from the World Development Indicators. Results: Of the 20 countries, UK topped the ageism table, while Sri Lanka had the lowest ageism score. Multiple regression models showed that higher levels of masculinity and long-term orientation are associated with ageism, controlling for other cultural dimensions, demographics (size and speed of aging), and economics (GDP-per-capita). Discussion: Our findings blunt the deterministic nature of ageism at the societal level. Demographics is only one side of the ageism coin, and the cultural side is equally, if not more important. This study lays the groundwork to tackle societal ageism—one of our generation's most pernicious threats.